A BIM-based space-oriented solution for hospital facilities management. Issue 11 (7th June 2021) - Wen, Ya; Tang, Llewellyn C.M.; Ho, Daniel C.W.
Abstract : Purpose: This paper aims to propose a space-oriented solution as an interface enabling the knowledge transfer between the building and the facilities management (FM) industry. Design/methodology/approach: The research gap is explored based on practical investigations in six large-scale hospitals in China. The theory of engineering systems integration inspires the proposed solution. A practical scenario is demonstrated to explain the workflow of this solution. Findings: It is founded that lagging information updates of FM systems in hospital project are one of the main reasons for inefficient and costly FM workflow. Building information modelling (BIM) model could provide accurate building information to the FM systems at the building handover stage. However, few researchers focus on the continuous information transfer solution from the BIM model to FM systems during the building in-use phase. An interface should be established for the "conversation" between the frequent changes of building and the FM systems in the post-construction period. Practical implications: The information updates in three FM systems due to space changes in a hospital project is considered as a practical scenario in this paper. It is presented with the workflow and the data logic chain. Originality/value: The originality of this paper is to propose a solution to integrate the space information provided by the BIM model with the parameters of particular FM systems. This solution deploys a BIM model for the FM industry. The solution could allow the FM personnel to ease operations and maintenance workflow by updating the space information in the BIM model.